Using a choice experiment and birder preferences to guide bird‐conservation funding. Issue 4 (29th May 2017) - Steven, Rochelle; Smart, James C. R.; Morrison, Clare; Castley, J. Guy
Abstract: Conservation of biodiversity, including birds, continues to challenge natural‐area managers. Stated‐preference methods (e.g., choice experiment [CE]) are increasingly used to provide data for valuation of natural ecosystems. We used a CE to calculate birders' willingness to pay for different levels of bioecological attributes (threatened species, endemic species, and diversity) of birding sites with hypothetical entry fees. The CE was delivered at popular birding and avitourism sites in Australia and the United Kingdom. Latent‐class modeling results revealed heterogeneous preferences among birders and correspondingly variable willingness to pay. Four clear groups were apparent: quantity‐driven birders, special‐birds seekers, confused respondents, and price‐is‐no‐object birders. Quantity‐driven birders were attracted to sites that deliver high levels of diversity and endemic species for which they were willing to pay 135 and 66 to visit, respectively, above what they were willing to pay to visit a site with low levels of diversity and few endemic and threatened species . Special‐bird seekers valued threatened species and high levels of endemic species most (willingness to pay 45 and 46, respectively). Confused respondents' preferences were difficult to determine, but they were the most sensitive to the hypothetical entry fees, unlike the price‐is‐no‐object birders, who were not at all sensitive to cost. Our findings demonstrate that birders are amenable to paying for their preferred birding experience. These payments could provide an alternative source of funding in some avitourism sites on both public and private land. Such alternative revenue streams should be explored and given full consideration in increasingly competitive conservation‐financing environments.